Selection of optimal bending types in die process of L-shaped panels considering the springback behaviours - Rozeman, Salfarina (Deer Hill Publications, 2024)
In die design, one of the most crucial decisions is selecting the appropriate die process to produce panels. The challenge for die designersis to understandthe behaviour of the panel material in relation to the die processes. If the die process is not correctly determined before die fabrication, severe panel spring back may occur, which can be difficult and require additional time and effort to rectify. Thispaper presents research aimed at understanding the behaviour of different bending process combinations concerning springback occurrence during the stamping process of an L-shaped design intent panel.Using simulation and experimentation, three types of materials with different tensile properties270 MPa, 440 MPa and 590 MPawith the similar thickness of 1.8 mm, were selected. The results were compared, analysed and optimized using Response Surface Methodology (RSM). The findingsdemonstrate that one-process bending with full bending (compress type) approach is the most suitable for producingL-shaped panels from the three material types.The study provides guidelines for die design engineers, industrial practitioners and researchers to decide on the best approach for die process decisionswhen dealing with specific panels properties, shape and thickness.